El Sacramentari II de Gellona (Montpellier, Bib. Mun., ms. 18) - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2012)
The Sacramentary Gellona II is the manuscript Montpellier, Bib. Mun., ms. 18. It was written between the years 1000-1025 in the same monastery of Gellona, nowadays Saint-Gulhem-le-Désert, for the use of its monastic community. It is the most ancient sacramentary integrally preserved in the whole ecclesiastic province of Narbone. It has the peculiarity of presenting the sources of all the Carolingian sacramentaries Gregorian, Aniane Supplement and Frankish Gelasian not yet completely merged, and this allows to follow the steps of the formation of later narbonnese sacramentaries. In the folia 206-207v, furthermore, it presents the list of the members of the Fraternitas Sancti Wilielmi started around the year 1100.